O samba urbano contemporâneo e sua desafricanização: um estudo sobre as transformações do samba no bairro da Lapa entre os anos de 2000 e 2017 - Dantas, Leila (2018)
The present work intends to analyze the process of desafricanization suffered by the urban samba played in the neighborhood of Lapa (Rio de Janeiro) between the years 2000 and 2007. Using thematic interviews of Oral History with important social actors who experienced the "resumption" and the decline of Lapa, this research intends to contribute to studies that analyze the different ways in which samba has been (and is) marginalized in Brazil, especially with regard to the elements that are directly linked to the African heritage and its Afro origin.